Effect of Al Hot-Dipping on High-Temperature Corrosion of Carbon Steel in N2/0.1% H2S Gas - Muhammad Ali Abro; Dong Bok Lee (Metals, 2016)
High-temperature corrosion of carbon steel in N2/0.1% H2S mixed gas at 600–800 °C for 50–100 h was studied after hot-dipping in the aluminum molten bath. Hot-dipping resulted in the formation of the Al topcoat and the Al-Fe alloy layer firmly adhered on the substrate. The Al-Fe alloy layer consisted primarily of a wide, tongue-like Al5Fe2 layer and narrow Al3Fe layer. When corroded at 800 °C for 100 h, the Al topcoat partially oxidized to the protective but non-adherent α-Al2O3 layer, and the interdiffusion converted the Al-Fe alloy layer to an (Al13Fe4, AlFe3)-mixed layer. The interdiffusion also lowered the microhardness of the hot-dipped steel. The α-Al2O3 layer formed on the hot-dipped steel protected the carbon steel against corrosion. Without the Al hot-dipping, the carbon steel failed by forming a thick, fragile, and non-protective FeS scale.